TLTRO III and banks' loan book rebalancing during the pandemic: Less "targeted" than intended forsome? - Claudio Corte Coi; Aristeidis Dadoukis; Hannah S. Hempell; Elena Rancoita (European Central Bank (ECB), 2025)
Targeted longer-term refinancing operations (TLTROs) helped supporting bank lending to firms and to households in the course of the COVID-19 pandemic. The use of TLTRO funding for mortgage loans to households had explicitly not been included into the targeted loan categories of these schemes, thereby, limiting potential unintended side effects on residential real estate markets. This paper, by means of an empirical analysis, assesses the impact of the relaxation of TLTRO III conditions at the beginning of the COVID-19 pandemic on euro area banks' loan portfolio composition. Our findings suggest that the targeted funding instrument under the relaxed pandemic conditions might, to some extent, have contributed to further fuelling residential real estate vulnerabilities, especially for banks in already vulnerable countries. Our results also contribute to the discussion on policy design and the preservation of the targeted nature of such support measures going forward and their interaction with financial stability.
Keywords: E52; E58; G01; G21; G28; 330; COVID-19 pandemic; unconventional monetary policy; TLTRO; residential real estate; loan; coronavirus disease; real estate credit; monetary policy; financial stability; financial risk; euro area